Enzyme-free and DNA-based universal platform for the construction of various logic devices based on graphene oxide and G-quadruplex. (December 2020) - Wang, Yue; Wei, Yani; Zhang, Yingying; Wang, Luhui; Dong, Yafei
Graphical abstract: A universal and enzyme-free platform has been ingeniously designed based on G-quarduplex and Graphene oxide (GO). We constructed a series of basic binary logic gates (AND. OR. INHIBIT. XOR) that benefit from the quenching property of GO to TAMRA and fluorescence enhancement generated by the specific binding of G-quadruplex to NMM. After that, using the same platform as the basis, two complex logic gates were implemented successfully, namely, half adder and half subtractor. Abstract: In the fields of biocomputing and biomolecular, DNA molecules are applicable to be regarded as data of logical computing platform that uses elaborate logic gates to perform a variety of tasks. Graphene oxide (GO) is a type of novel nanomaterial, which brings new research focus to materials science and biosensors due to its special selectivity and excellent quenching ability. G-quadruplex as a unique DNA structure stimulates the intelligent application of DNA assembly on the strength of its exceptional binding activity. In this paper, we report a universal logic device assisted with GO and G-quadruplex under an enzyme-free condition. Integrated with the quenching ability of GO to the TAMRA (fluorophore, Carboxytetramethylrhodamine) and the enhancement of fluorescence intensity produced by the peculiar binding of G-quadruplex to the NMM (N-methylmesoporphyrin IX), a series of basic binary logic gates (AND. OR. INHIBIT. XOR) have been designed and verified through biological experiments. Given the modularity and programmability of this strategy, two advanced logic gates (half adder and half subtractor) were realized on the basis of the same work platform. The fluorescence signals generated from different input combinations possessed satisfactory results, which provided proof of feasibility. We believe that the proposed universal logical platform that operates at the nanoscale is expected to be utilized for future applications in molecular computing as well as disease diagnosis.